2016
DOI: 10.1681/asn.2016010012
|View full text |Cite
|
Sign up to set email alerts
|

Targeting eIF5A Hypusination Prevents Anoxic Cell Death through Mitochondrial Silencing and Improves Kidney Transplant Outcome

Abstract: The eukaryotic initiation factor 5A (eIF5A), which is highly conserved throughout evolution, has the unique characteristic of post-translational activation through hypusination. This modification is catalyzed by two enzymatic steps involving deoxyhypusine synthase (DHPS) and deoxyhypusine hydroxylase (DOHH). Notably, eIF5A may be involved in regulating the lifespan of during long-term hypoxia. Therefore, we investigated the possibility of a link between eIF5A hypusination and cellular resistance to hypoxia/ano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
76
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(96 citation statements)
references
References 40 publications
(46 reference statements)
7
76
0
4
Order By: Relevance
“…In kidney cells, the importance of EIF5A-hypusination on mitochondrial protein expression was also observed [63]. Melis et al [63] showed that inhibition of hypusination by intraperitoneal injection of rats with the deoxyhypusine synthase inhibitor N1-guanyl-1,7-diaminoheptane (GC7) led to decreased expression of mitochondrial complexes. This correlated with lower mitochondrial respiration [63].…”
Section: Polyamines Induce Mitochondrial Protein and Gene Transcriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…In kidney cells, the importance of EIF5A-hypusination on mitochondrial protein expression was also observed [63]. Melis et al [63] showed that inhibition of hypusination by intraperitoneal injection of rats with the deoxyhypusine synthase inhibitor N1-guanyl-1,7-diaminoheptane (GC7) led to decreased expression of mitochondrial complexes. This correlated with lower mitochondrial respiration [63].…”
Section: Polyamines Induce Mitochondrial Protein and Gene Transcriptionmentioning
confidence: 99%
“…Melis et al [63] showed that inhibition of hypusination by intraperitoneal injection of rats with the deoxyhypusine synthase inhibitor N1-guanyl-1,7-diaminoheptane (GC7) led to decreased expression of mitochondrial complexes. This correlated with lower mitochondrial respiration [63]. The decrease in mitochondrial respiration lead to lower reactive oxygen species (ROS) production during hypoxia.…”
Section: Polyamines Induce Mitochondrial Protein and Gene Transcriptionmentioning
confidence: 99%
“…These findings suggest that inhibition of hypusination through substrate competition at DHPS is possible. GC7 has been extensively studied as an antitumor agent (reviewed by Nakanishi and Cleveland, 2016), as well as in vivo for several applications (Imam et al, 2014;Melis et al, 2016), so animal model testing of GC7 efficacy is a logical next step in investigating the importance of eIF5A for virus replication and pathogenesis.…”
mentioning
confidence: 99%
“…L'activation de eIF5A nécessite l'action successive de la DHS (10) Les paramètres physiologiques ont été suivis sur une période de 3 mois. Chez les animaux témoins, l'ischémie reperfusion a provoqué à court et long terme une altération de la fonction rénale de l'organe greffé, comme l'indique le temps de récupération de la diurèse, l'excrétion fractionnelle de sodium, l'osmolarité de l'urine ou encore l'excrétion d'alanine aminopeptidase [13]. Chez les animaux préalablement traités au GC7, l'ultrastructure du rein est restée nettement mieux préservée ( Figure 4B), le taux de cellules apoptotiques a été diminué, le stress oxydatif ( Figure 4C) et la peroxydation des lipides se sont maintenus à un bas niveau et 3 https://www.sciencedirect.com/topics/medicine-and-dentistry/viaspan…”
Section: Représentation Schématique Du Nouveau Concept Pharmacologiunclassified
“…L'ischémie ainsi réalisée induit une augmentation de l'excrétion fractionnelle de sodium ( Figure 3B), de phosphate et de glucose [13], ainsi que l'apparition dans les urines du marqueur de l'atteinte tubulaire NGAL (neutrophil gelatinase-associated lipocalin) ( Figure 3C) L'altération de ces paramètres reflète une atteinte drastique du tubule proximal, qui est majoritairement en charge de la gestion de ces ions et des métabolites. Le traitement préalable au GC7 empêche de façon importante la dégradation de ces paramètres, indiquant un effet protecteur vis-à-vis de la privation d'oxygène ( Figure 3B, C) [13]. Ce résultat fondamental démontre donc que la translation vers le mammifère du concept mis en évidence chez la drosophile est possible et que les voies mises en jeu semblent très conservées entre ces deux espèces.…”
Section: Représentation Schématique Du Nouveau Concept Pharmacologiunclassified